ICT Literacy and Problem Solving Skill of Senior High School through Discovery Learning Assisted by Moodle - Thorieq Moh. Yusuf; Wartono Wartono; Supriyono Koeshandayanto (Jurnal Pendidikan Sains, 2018)
Abstract: This research has an explanatory mixed method design which aims to analyze the influence of discovery learning assisted by moodle on the problem-solving skills and ICT literacy of SMA Negeri 1 Purwoharjo student. The research subjects consisted of 37 XI grade students from each experimental class and the control class. Instruments test in the form of 5 description questions to measure problem-solving abilities and performance questionnaires to measure ICT literacy skills. The results of the manova statistical test showed that the value of wilks lamda has Sig. (0.005) < (0.05). This shows that discovery learning assisted by moodle influences ICT problem solving and literacy ICT skills.Key Words: problem-solving skills, ICT literacy, discovery learning, moodle Abstrak: Penelitian ini memiliki desain mixed method explanatory yang bertujuan untuk menganalisis pengaruh pembelajaran discovery berbantuan moodle terhadap kemampuan pemecahan masalah dan literasi ICT siswa SMA Negeri 1 Purwoharjo. Subjek penelitan terdiri atas 37 siswa kelas XI dari masing-masing kelas eksperimen dan kelas kontrol. Instrumen test berupa 5 soal uraian untuk mengukur ke-mampuan pemecahan masalah dan angket performen untuk mengukur kemampuan literasi ICT. Hasil dari uji statistik manova didapatkan nilai wilks lamda sebesar Sig. (0,005) < (0,05). Hal tersebut menunjuk-kan bahwa pembelajaran discovery berbantuan moodle berpengaruh terhadap kemampuan pemecahan masalah dan literasi ICT.Kata kunci: kemampuan pemecahan masalah, literasi ICT, pembelajaran discovery, moodle